FORMULATION OF NOVEL ANTI-CANCER SOLID LIPID NANO-PARTICLES (International Journal of Food and Nutritional Sciences, 2022)
Abstract- A human prostate cancer cell line known as LNCaP was used in this study to investigate the anti-cancer effects of CRC-encapsulated SLN formulations, both loaded and unloaded. CRC encapsulated SLN (CRC-SLN) demonstrated anti-tumor action, whereas blank SLN (BL-SLN) did not show any evidence of anti-tumor activity. At a concentration of 100 g/ml of CRC, both lipid-based and non-lipid-based CRC-loaded SLNs decreased the viability of LNCaP cells to practically 0%. Studies that investigated cellular uptake provided evidence that CRC-SLN was taken inside the cell, where it was discovered to be positioned in the cytoplasm close to the nucleus. Studies using flow cytometry provided evidence that CRC-SLNs had the capacity to induce both early and late stages of the apoptotic process. An increased level of anticancer activity was observed in retinoic acid (RTA) loaded SLN that had been adjusted by adjusting the process parameters (pressure and temperature) and making use of a variety of lipid grades to form nano-dispersions. High-pressure homogenization was used to form the RTA-SLN dispersions, which were then studied in terms of particle size, zeta potential, drug entrapment efficiency, transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD), and in vitro drug release. The effectiveness of the anticancer treatment was determined by incubating RTA-SLN with LNCaP cells.